PERAN FILSAFAT DALAM KEBHINEKAAN KEBERAGAMAN MASYARAKAT - Nuraini; Dalilan (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2023)
This study is done because there are still many problems or conflicts due to diversity in the community environment such as cultural differences, differences between individuals, social changes, and so on. It can be said to be a potential because Indonesia has abundant wealth, both natural and cultural and language wealth. This method uses a quantitative approach, the method used is a Literature (library research) study used by collecting data by looking for sources from various books, articles, journals and research. The results and discussion of this study show that philosophy is very active in making demonization of the society. But from the results concluded that philosophy plays an important role in aligning community diversity by providing frameworks to understand and respect different world perspectives and views such as, understanding the nature of diversity, developing critical thinking skills, fostering ethics and moral, creating the same language. Philosophy helps the community to appreciate the values and importance of different experiences of society and to recognize the value and importance of diversity. By questioning the assumptions and examining the fundamental values and principles that guide the mind and behavior of the community, philosophy helps identify and challenge tendencies that perpetuate inequality and discrimination.